ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PADA PT. BANK PERKREDITAN RAKYAT PRISMA DANA MANADO - Ham, Ferry Christian; Karamoy, Herman; Alexander, Stanly (Universitas Sam Ratulangi, 2018)
Revenue is the value derived from the activities of a company known by different names such as sales, service income, interest, profit sharing, royalties and rent. Expenses represent a reduction in usage life during an accounting period in the form of cash outflow or loss of assets or occurrence of liabilities resulting in a decrease in equity not related to the distribution to investors. Recognition of income at PT. Bank Credit Prisma Dana Manado recognizes income based on the accrual basis and cash basis method, where accrual basis income is recognized as incurred while cash base income is recognized upon receipt of cash. Load recognition at PT. Bank Credit Prisma Dana Manado recognize expenses based on the accrual basis method, in which the accrual basis is recognized as an expense in the statements of income in the period in which they are incurred. The research method used in this thesis research is descriptive method whose purpose every data collected is analyzed and then drawn a conclusion and research type used is qualitative descriptive. The results obtained that the recognition of income and expenses at PT. Bank Credit Prisma Dana Manado Rural Bank is in compliance with PSAK No. 23, because PSAK No. 23 only recognizes two methods: accrual basis and cash base.Keywords: Analysis, Revenue Recognition, Expense Recognition.